Phytoplankton Diversity as Bioindicator of Pandanduri Dam Waters, East Lombok Regency - Lalu Hasan Nasirudin Zohri; Agil Al Idrus; Lalu Japa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2020)
Pandanduri Dam waters has an essential function for the community made the activities of the surrounding community inseparable from the Pandanduri Dam that made potentially quality change of the Pandanduri Dam waters. Good water quality is an important requirement for humans that made water quality research is essential to be done. Human activities will affect environmental factors such as biological parameters, especially phytoplankton, which are indicators of water quality. The aim of this study was to analyzed water quality of Pandanduri Dam through study of phytoplankton community and diversity. Sample sites were determined based on haphazard sampling method and phytoplankton data were analyzed based on the shannon-weiner diversity index. The results showed that the phytoplankton community identified in Pandanduri Dam consisted of 5 classes, 13 orders, and 31 species withÃÂ species diversity index of 2,659. Based on fitoplankton diversity index value the water ofÃÂ Pandanduri Dam was in lightly polluted category. It is suggested to more detailed studies should be undertaken especially on species that produce toxins over a longer time scale.